O celular na sala de aula: possibilidade para os multiletramentos na educaçao de jovens e adultos - Falcão, Sayonara Leite (2017)
Inclusion of mobile phone devices as part of pedagogical actions in classroom, promoting digital inclusion in teaching/learning process, is the object of analysis of this study. This has been applied in six different classes of first cycle of Educação de Jovens e Adultos – EJA (Youth and Adult Education) of public school from Boa Vista – PB. Grounded on the pedagogical theory from Paulo Freire, this is a qualitative research, also based on applied linguistics beyond digital culture and teaching. The theory of this study is based on the liberating bases of popular education and it has been sought contributions in studies on both digital technologies and information, beyond multiliteracy, creating a dialogue between researchers from several fields of knowledge, such Freire (2011) Kleiman (2005), André (2008), Alves (1991), Gonsalves (2001), Gil (2002), Kenski (2012) Rojo (2012), aiming to compose a favorable scenario to the construction of writing and the inclusion of digital technologies in the EJA. The methodologies used the following procedures: Observation of participant members; Planning of pedagogical actions; Interventions in reading; Construction of both alphabetical writing and digital literacy in EJA classes. The data analysis was developed through class diaries, filming and photographs, beyond interviews and questionnaires, in which the teachers reflected on the teaching practice. Interactive processes were observed in the field of multiliteracies involved in using mobile device. In the interpretations of the first data were considered the implication factors of the practices of literacy beyond skills in using of mobile phone, converging towards the effective construction of writing and digital inclusion, in which it was found respect for the diversity present in EJA.The analysis allowed the perception of teaching action, directed to the writing construction, it is only limited to practices aimed at appropriation of alphabetic writing system and normativity, in which it often ends by dissociating itself from the social uses of writing. It has been common to move away from literacy and pedagogical practices of digital inclusion, verifying necessity for studies that, going beyond the scientific explanations, require practical actions, in a given context and thus contributes to both writing construction and social inclusion for young people and adults, which historically suffer exclusion in the educational process. From these conclusion emerges up a didactic sequence, including activities using mobile device, which was both built and executed in these classes, making possible the digital inclusion in experience in the first cycle of the EJA.